2017
DOI: 10.1016/j.ijpara.2016.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the distribution of haemosporidian parasites within an oceanic island

Abstract: 20Understanding how different ecological and evolutionary processes influence the distribution of 21 pathogens within the environment is important from many perspectives, including for wildlife 22 epidemiology, evolutionary ecology and conservation. The simultaneous use of ecological and 23 evolutionary frameworks together can enhance our conceptual understanding of host-parasite 24 interactions, however such studies are rare in the wild. Using samples from 12 bird species caught 25 across all habitats existin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
49
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 98 publications
4
49
0
4
Order By: Relevance
“…We found, however, that the proportion of individuals infected was similar between wet and dry seasons, suggesting little influence of seasonality on prevalence patterns. Likewise, although temperature has been shown to be an important predictor of prevalence across environmental gradients (Padilla et al., ; Zamora‐Vilchis, Williams, & Johnson, ), the lack of significant variation in temperature across the Magdalena River Valley (Appendix ) suggests that, at least at the spatial scale of our study, temperature likely has similar effects on infection probability across the Magdalena River Valley. However, we acknowledge that complex interactions among temperature, water availability, and vector abundance at local scales might partly explain variability in haemosporidian prevalence in birds.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…We found, however, that the proportion of individuals infected was similar between wet and dry seasons, suggesting little influence of seasonality on prevalence patterns. Likewise, although temperature has been shown to be an important predictor of prevalence across environmental gradients (Padilla et al., ; Zamora‐Vilchis, Williams, & Johnson, ), the lack of significant variation in temperature across the Magdalena River Valley (Appendix ) suggests that, at least at the spatial scale of our study, temperature likely has similar effects on infection probability across the Magdalena River Valley. However, we acknowledge that complex interactions among temperature, water availability, and vector abundance at local scales might partly explain variability in haemosporidian prevalence in birds.…”
Section: Discussionmentioning
confidence: 59%
“…We found, however, that the proportion of individuals infected was similar between wet and dry seasons, suggesting little influence of seasonality on prevalence patterns. Likewise, although temperature has been shown to be an important predictor of prevalence across environmental gradients (Padilla et al, 2017;Zamora-Vilchis, Williams, & Johnson, 2012), the lack of significant variation in temperature across the Magdalena River…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In earlier years, approximately half of the samples were collected from the high‐altitude (>2,000 m above sea level) plateau of El Teide. Malaria has not been found in Berthelot's pipits in this location (González‐Quevedo et al, ; Illera et al, ; Spurgin et al, ), although a survey of passerine communities on Tenerife found malaria at low frequency in high‐altitude habitats (Padilla et al, ). The relationship seen in 2011 between TLR4_P1 and infection may be masked in other sampling years by the increase in uninfected individuals from areas of low malaria abundance.…”
Section: Discussionmentioning
confidence: 91%
“…Because of the generally low prevalence and diversity of the hemosporidian parasites on islands (Hellgren, Križanauskienė, Hasselquist, & Bensch, ; Martínez‐de la Puente et al, ; Padilla, Illera, Gonzalez‐Quevedo, Villalba, & Richardson, ; Pérez‐Rodríguez, Ramírez, Richardson, & Pérez‐Tris, ; Sari, Klompen, & Parker, ) and the presence of only one potential vector species on the island, we expected to find an essentially simple host‐vector‐parasite system. However, we found that the opportunistic feeding behavior of louse flies resulted in an unexpected massive transmission of haemosporidians from kills to falcons’ louse flies.…”
Section: Discussionmentioning
confidence: 99%